5-Hydroxymethylcytosine (5-hmC) Specific Enrichment - Szulwach, Keith E (Bio Protoc, 2012)
5-Hydroxymethylcytosine (5-hmC) is a newly discovered DNA modification in mammalian genomes. This protocol is to be a highly efficient and selective chemical approach to label and capture 5-hmC, taking advantage of a bacteriophage enzyme that adds a glucose moiety to 5-hmC specifically, which could in turn be used for high-throughput mapping via next-generation sequencing.